A four carbon organonitrate as a significant product of secondary isoprene chemistry - Hallquist, Mattias; Tsiligiannis, Epameinondas (University of Gothenburg, 2021)
Oxidation of isoprene by nitrate radicals (NO3) or by hydroxyl radicals (OH) under high NOx conditions forms a substantial amount of organonitrates (ONs). ONs impact NOx concentrations and consequently ozone formation while also contributing to secondary organic aerosol. Here we show that the ONs with the chemical formula C4H7NO5 are a significant fraction of isoprene-derived ONs, based on chamber experiments and ambient measurements from different sites around the globe. From chamber experiments we found that C4H7NO5 isomers contribute 5-17% of all ONs formed during nighttime and constitute more than 40% of the ONs after further daytime oxidation. In ambient measurements C4H7NO5 isomers usually dominate both nighttime and daytime, implying a long residence time compared to C5 ONs which are removed more rapidly. We propose potential nighttime sources and secondary formation pathways, and test them using a box model with an updated isoprene oxidation scheme.

This dataset is based on oxidation experiments of isoprene + NO3 radicals at the atmospheric chamber SAPHIR, in Jülich, Germany and ambient data from five different locations. More specifically, this dataset is provided in order for users to be able to replicate the results from the Tsiligiannis et al. publication. It includes time-series of gaseous species.

The files called I-CIMS contain compounds that measured using a chemical ionization mass spectrometer (CIMS) with iodide as the reagent ion. The files called Br-CIMS contain compounds that measured using a chemical ionization mass spectrometer (CIMS) with bromide as the reagent ion. The files called TD-CRDS contain the total alkyl nitrates measured using a thermal dissociation−cavity ring-down spectrometer.
The chamber data are indicated by the date of the experiment (e.g. 9Aug). The ambient data are indicated by the location where they collected (e.g. Amazon).

All the date & time data corresponds to local time. For each column, the naming e.g. "BrC4H7NO5_ncps" or "C4H7INO5_ppt", corresponds to the chemical formula of the compound (C4H7NO5) clustering with either bromide or iodide, and the measurement units (ncps=normalized counts per second) or (ppt=parts per trillion by volume). File delimiter is the tabstop.

The data from the SOAS campaign can be found here:
https://csl.noaa.gov/groups/csl7/measurements/2013senex/Ground/DataDownload/index.php?page=/groups/csl7/measurements/2013senex/Ground/DataDownload/

Oxidation av isopren med nitratradikaler (NO3) eller av hydroxylradikaler (OH) under höga NOx-förhållanden bildar en betydande mängd organonitrater (ON). ON påverkar NOx-koncentrationerna och följaktligen ozonbildningen samtidigt som de bidrar till sekundär organisk aerosol. Här visar vi att ON med den kemiska formeln C4H7NO5 är en betydande del av isopren-härledda ON, baserat på kammarexperiment och omgivningsmätningar från olika platser runt om i världen. Från kammarexperiment fann vi att C4H7NO5 isomerer bidrar med 5-17% av alla ON som bildas under natten och utgör mer än 40% av ON efter ytterligare dagtid oxidation. I omgivningsmätningar dominerar vanligtvis C4H7NO5-isomerer både nattetid och dagtid, vilket innebär en lång uppehållstid jämfört med C5-ON som tas bort snabbare. Vi föreslår potentiella nattkällor och sekundära bildningsvägar och testar dem med en boxmodell med ett uppdaterat isoprenoxidationsschema.

Se den engelska sidan för beskrivning av datasetet.
En organonitrat med fyra kolatomer som en betydande produkt av sekundär isoprenkemi
Keywords: nitrogen oxides; kväveoxider; atmospheric ozone; atmosfäriskt ozon; Atmospheric conditions; Atmosfäriska förhållanden; Organonitrate; Organonitrat; Isoprene; Isopren; Environmental Sciences; Miljövetenskap; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Geoscientific Information; Geovetenskap; Environment; Miljö